Significance of Mid-Miocene volcanism in northeast Nevada: petrographic, chemical, isotopic, and temporal importance of the Jarbidge Rhyolite - Callicoat, Jeffrey Scott (Kansas State University, 2010)
The Jarbidge Rhyolite of Elko County, Nevada, is approximately 26 mapped bodies of porphyritic rhyolite. Several of the bodies are truncated by the Idaho or Utah border, and extend into the states for an unknown distance. This study focuses on five bodies, the Mahoganies, two near Wild Horse Reservoir, the outcrop enclosing the Jarbidge Mountains, and one outcrop south of Wells. The study’s focus is providing field, petrography, geochemistry, oxygen isotope, and geochronology information about the five previously mentioned bodies. Physical volcanology encountered during this study indicates the sampled Jarbidge Rhyolite are effusive lava flows and domes that coalesced over the life of the volcanic system. First order approximations indicate that erupted products cover ~1,289 km2 and erupted material totals ~509 km3. Petrography indicates primary anhydrous mineral assemblages, assimilation of granitoid, possible assimilation of metamorphic rock and magma mixing of mafic and silicic bodies. Collectively, the Jarbidge Rhyolite lava flows sampled are compositionally restricted from rhyolite to high silica rhyolite and all samples demonstrate A-type magma characteristics. Compositions from different bodies overlap on Harker diagrams, and trace element ratios distinguish few flows from the other samples. Rare earth element patterns mimic one another, and incompatible trace element ratios overlap between bodies, likely indicating the presence of one large magma body. Oxygen isotope values for selected samples range 6.61-8.95%oVSMOW are coincident with normal igneous values. New 40Ar/39Ar geochronology indicates Jarbidge Rhyolite volcanism initiated ca. 16.7 Ma near Wild Horse Reservoir and was active at Bear Creek Summit ca.15.8 Ma. Local Steens Basalt, geochemistry, and Au-Ag mineralization indicate Jarbidge Rhyolite is similar to Middle Miocene silicic volcanics (e.g. Santa Rosa-Calico volcanic field) further west in the Oregon-Idaho-Nevada tristate region.
Keywords: Jarbidge rhyolite; Middle miocene volcanism; Geology (0372)